Pengaruh Komunikasi Interpersonal dan Pengembangan Karier serta Peran Motivasi Berprestasi sebagai Variabel Moderasi terhadap Kinerja Dosen DPK LLDIKTI Wilayah VII Jawa Timur: The Influence of Interpersonal Communication and Career Development and the Role of Achievement Motivation as a Moderating Variable on the Performance of Lecturers at the DPK LLDIKTI Region VII, East Java - Suyono Suyono (CV ODIS, 2026)
This study aims to analyze the influence of interpersonal communication on the career development and performance of lecturers and examine the role of achievement motivation as a moderating variable in the relationship between career development and performance of lecturers at the Regional Lecturers Association (DPK) of the Indonesian Higher Education Institution (LLDIKTI) Region VII, East Java. The study used a quantitative approach with explanatory research methods. The study sample consisted of lecturers at the Regional Lecturers Association (DPK) of the Indonesian Higher Education Institution (LLDIKTI) Region VII, East Java, selected using proportional random sampling. Data analysis was performed using Structural Equation Modeling (SEM). The results showed that interpersonal communication had no significant effect on career development (?=0.196; p=0.252) or lecturer performance (?=0.085; p=0.277). Career development also had no direct effect on lecturer performance (?=0.007; p=0.808). However, achievement motivation was shown to positively moderate the relationship between career development and lecturer performance (CR=3.929; p<0.001), indicating that the higher the achievement motivation, the stronger the contribution of career development to improving lecturer performance.The research findings indicate that career development does not automatically improve lecturer performance; rather, its effectiveness is largely determined by the lecturer's level of achievement motivation. Therefore, career system development in higher education needs to be integrated with strategies to increase achievement motivation to optimally improve lecturer performance.